Improving the dyeability of polyolefin fibres by microwave heating - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2014)
Recently, extensive research has been carried Out using microwave energy in the textile wet processes due to the many potential advantages such as energy saving, reduced processing time and improved product quality. Polypropylene is a significant polyolefin fibre with a relatively low price, hydrophobic properties and resistance to staining and many chemicals. However, this fibre is difficult to dye by means of the conventional dyeing techniques, because its molecular structure lacks dye receptor sites. In this work, microwave heating was utilized in the exhaust dyeing of polypropylene to enhance the dyeability of the fibre by specially selected disperse dyes. The results were compared with the conventional dyeing's results. Dyeing techniques were compared in terms of colour yields, fastness values and tensile strengths of the dyed fibres. Microwave heating shortened the dyeing time and the colour yield was improved.
Keywords: polypropylene; microwave dyeing; exhaust dyeing; synthetic fibres; EASY CARE; COTTON; IRRADIATION; FABRICS; ENERGY